Positive Psychological Micro-Interventions to Improve the Work–Family Interface: Use Your Resources and Count Your Blessings - Peeters, Maria C. W.; van Steenbergen, Elianne F.; Ybema, Jan Fekke (Frontiers in Psychology, 2020)
The present study is designed to test the effectiveness of two positive psychological micro-interventions (‘use your resources’ and ‘count your blessings’) aimed at improving the combination of work and family roles. Based on the Transactional Model of Stress, the Conservation of Resources Theory and the Work-Home Resources Model, it was expected that the interventions would result in a more positive cognitive appraisal of combining both roles as well as in less work-to-family and family-to-work conflict and more work-to-family and family-to-work enrichment. The hypotheses were tested in a field experiment with three conditions and three measurement waves. In total, 218 working mothers participated in the study. The ‘use your resources’ intervention appeared effective in sorting positive effects on the work-family outcome variables measured. Participating in the ‘count your blessing’ micro-intervention did not result in a better (appraisal of the) combination of work and family roles. Moreover, for generating positive effects it was important that the participants performed the exercises on a regular basis: the more days women performed the exercise, the stronger the effects. The implications of our findings for future interventions to improve work-family role combining are discussed.